2011
DOI: 10.1093/bja/aer160
|View full text |Cite
|
Sign up to set email alerts
|

Complex procedural skills are retained for a minimum of 1 yr after a single high-fidelity simulation training session

Abstract: After a single simulation training session, improvements in cricothyroidotomy skills are retained for at least 1 yr. These findings suggest that high-fidelity simulation training, along with practice and feedback, can be used to maintain complex procedural skills for at least 1 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(52 citation statements)
references
References 25 publications
6
42
0
2
Order By: Relevance
“…The effectiveness and retention of other skills taught in the SBME setting have been studied less, and much heterogeneity is seen with regards to performed skills, study subjects and teaching methods, rendering data interpretation difficult. Examples include competencies in laparoscopic surgery or colonoscopy by surgical residents after 3 months [13,19], a significant decay in temporary haemodialysis catheter insertion skills by nephrology fellows after 6 months [20] and a satisfactory retention of a rare but crucial procedural skill like coniotomy performed by trained anaesthetist up to one year [21]. This heterogeneity in findings makes it hard if not impossible to draw any conclusions for skills lab training in medical undergraduates.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness and retention of other skills taught in the SBME setting have been studied less, and much heterogeneity is seen with regards to performed skills, study subjects and teaching methods, rendering data interpretation difficult. Examples include competencies in laparoscopic surgery or colonoscopy by surgical residents after 3 months [13,19], a significant decay in temporary haemodialysis catheter insertion skills by nephrology fellows after 6 months [20] and a satisfactory retention of a rare but crucial procedural skill like coniotomy performed by trained anaesthetist up to one year [21]. This heterogeneity in findings makes it hard if not impossible to draw any conclusions for skills lab training in medical undergraduates.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Crofts et al demonstrated that acquired skill at managing shoulder dystocia in obstetrics is largely maintained up to 12 months post-SBME training among midwives and doctors in the UK[38]. Boet and coauthors have shown effects to last for 1 year[39].…”
Section: Does It Work?mentioning
confidence: 96%
“…Most procedural skills are taught during patient-based encounters as the clinical need arises 2. Some procedures are commonly encountered in the clinical environment, such as central venous lines, endotracheal intubation, and laceration repair; while others appear to be more rarely encountered, including needle thoracentesis, cricothyroidotomy, and urgent thoracotomy for trauma 3. This may be because the indications for such procedures require a very specific clinical scenario, which may be rare, or the procedure itself may be a last ditch effort to save a patient’s life.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of high fidelity simulations, simulated patients, and anatomic simulators are well-documented 37. The most common high fidelity simulations use manikins with realistic features responding physiologically to interventions and performance of procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation